5x+5-3x+3=7x+3-x+6

Simple and best practice solution for 5x+5-3x+3=7x+3-x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+5-3x+3=7x+3-x+6 equation:


Simplifying
5x + 5 + -3x + 3 = 7x + 3 + -1x + 6

Reorder the terms:
5 + 3 + 5x + -3x = 7x + 3 + -1x + 6

Combine like terms: 5 + 3 = 8
8 + 5x + -3x = 7x + 3 + -1x + 6

Combine like terms: 5x + -3x = 2x
8 + 2x = 7x + 3 + -1x + 6

Reorder the terms:
8 + 2x = 3 + 6 + 7x + -1x

Combine like terms: 3 + 6 = 9
8 + 2x = 9 + 7x + -1x

Combine like terms: 7x + -1x = 6x
8 + 2x = 9 + 6x

Solving
8 + 2x = 9 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
8 + 2x + -6x = 9 + 6x + -6x

Combine like terms: 2x + -6x = -4x
8 + -4x = 9 + 6x + -6x

Combine like terms: 6x + -6x = 0
8 + -4x = 9 + 0
8 + -4x = 9

Add '-8' to each side of the equation.
8 + -8 + -4x = 9 + -8

Combine like terms: 8 + -8 = 0
0 + -4x = 9 + -8
-4x = 9 + -8

Combine like terms: 9 + -8 = 1
-4x = 1

Divide each side by '-4'.
x = -0.25

Simplifying
x = -0.25

See similar equations:

| 2n-16=-16 | | 21k^2-35k-8=-8 | | 7t-10=-16+8t | | ln(5x-2)-ln(3x-2)=ln(15x-6)-ln(5x+2) | | x+5x+6=29 | | 3(3S+1)=111 | | 8y+x=20 | | 3n^2-39n=-120 | | 3w-w=16 | | f(x)=-16x^2+96x+12 | | -5(x-6)=85 | | 4+10=22 | | r^2+7r+5=-7 | | 3(S+1)=36 | | 0=2x^2-32 | | -9w+8w+2=-3 | | 26m=650 | | 6(v-5)(5v+8)=0 | | 4(2L+1)=111 | | -11-n=-11 | | 3x+(x+38)=90 | | 14=5+h | | U-1=-4 | | -46=p-19 | | 8a-4-3a=12 | | 13-4x=-x-31 | | (x+54)+2x=90 | | 8x-4=-1 | | (x+54)+2x=180 | | 6(3x+5)=100 | | 6x+7c=37cforx | | 12x^2+105x+147=35 |

Equations solver categories